Respuesta :
Answer:
[tex] \sf :\implies \quad {\pmb{x = - 4}}[/tex]
Solution:
Let's solve the given equation step by step ;
[tex] \sf :\implies \quad 6(x + 4) + 1 = x + 5[/tex]
The first step is to distribute the equation:
[tex] \sf :\implies \quad (6 \times x ) + (6 \times 4) + 1 = x + 5[/tex]
[tex] \sf :\implies \quad 6x + 24 + 1 = x + 5[/tex]
[tex] \sf :\implies \quad 6x + 25 = x + 5[/tex]
Second step is to combine the like terms:
[tex] \sf :\implies \quad 6x + 25 - x = 5[/tex]
[tex] \sf :\implies \quad( 6x - x) + 25 = 5[/tex]
[tex] \sf :\implies \quad 5x + 25 = 5[/tex]
Now, subtract 25 from both sides :
[tex] \sf :\implies \quad 5x + 25 - 25 = 5 - 25[/tex]
[tex] \sf :\implies \quad 5x = - 20[/tex]
Divide both sides by 5:
[tex] \sf :\implies \quad \dfrac{5x}{5} = - \dfrac{20}{5} [/tex]
[tex] \sf :\implies \quad \boxed{ \pmb{\sf x = - 4}}[/tex]
Hence, your answer is ; x = -4